1984
DOI: 10.1055/s-2008-1044169
|View full text |Cite
|
Sign up to set email alerts
|

The Collateral Arterial Network of the Spleen following Ligation of the Splenic Artery in Traumatic Rupture of the Spleen; an Arteriographic Study

Abstract: Ligation of the splenic artery, combined with splenorrhaphy, was used successfully on eight children with splenic trauma involving major segmental vessels. Evaluation of the collateral arterial network and of its adequacy was done by means of arteriography on four out of the eight patients. Aortographies were carried out on the twentieth day, the first month, the third month, and the fourth month following the ligation. A collateral arterial network, deriving mainly from the short gastric arteries was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…PSAE involves occluding the proximal splenic artery using coils or, in some specific situations, using the Amplatzer ® vascular plug. It often can be performed using standard 4- to 5-French catheters and is usually less time-consuming than distal embolization [73, 74]. The technique of selective distal embolization (patient B; Figs.…”
Section: Diagnosticsmentioning
confidence: 99%
“…PSAE involves occluding the proximal splenic artery using coils or, in some specific situations, using the Amplatzer ® vascular plug. It often can be performed using standard 4- to 5-French catheters and is usually less time-consuming than distal embolization [73, 74]. The technique of selective distal embolization (patient B; Figs.…”
Section: Diagnosticsmentioning
confidence: 99%
“…In experimental studies, an increased arterial collateral network was detected at angiography after ligation and embolization of the main splenic artery after 2-4 months [16,30]. Another angiographic follow-up study after ligation of the splenic artery in four children revealed collaterals from the short gastric arteries, the left gastroepiploic artery, and splenic capsule arteries 20 days to 4 months after operation [15]. The significant increase in RI, S/D ratio, and AC at intermediate and late follow-up in our study is probably explained by this increase in collateral circulation.…”
Section: Discussionmentioning
confidence: 92%
“…Angiography immediately after embolization determines the technical success of the procedure. It is assumed that the underlying effect of the flow preservation is formation of collaterals as shown in experimental angiographic studies and some case reports in pediatric patients after ligation of the splenic artery [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The end point of proximal embolization, as in surgical artery ligation, is to reduce the splenic bleeding by decreasing blood flow in the main splenic trunk [14] SAE allows reduction in the intrasplenic arterial blood pressure, a condition that may help clots to organize and the spleen to heal [15]. Moreover, it is theorized that proximal embolization allows the spleen to remain, at least partially, perfused by collaterals, thus, limiting the risk of splenic infarction [16]. A series of CT examinations of embolized spleens has shown proximal embolization to be associated with less frequent and smaller infarcts than distal embolization [17].…”
Section: Discussionmentioning
confidence: 99%